The determination of "added mass" of swimmers as a part of studies of non-steady flow patterns - Klauck, J.; Ungerechts, B. E. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Swimmers displace mass of water because there cannot be two bodies which share the same space. Due to the cyclic interaction of body and water mass there are flow effects on the body beyond common consideration of thrust and drag known from steady flow mechanics which was developed for ship construction. A ship, with given shape, should not sink and not produce too much drag to keep the energy costs low. Concerning ships the 'hull' is separated from the propulsive propellers and flow effects are sufficiently described by using steady flow mechanics. In contrast, biological organisms produce thrust and resistance simultaneously during cyclic self-produced propulsion of bodies changing their body form. The cyclic actions prevent flow phenomena from being constant and changes of velocity (acceleration) influence the interaction effects profoundly. These time-space effects are better explained using non-steady flow physics which is not a synonym for turbulent flow of any boundary layer due to viscosity (Lighthill1969). Scarcely any publication on sport swimming or various activities in aquatic space is touching the flow effects of unsteady water mass. Change of motion of water mass cause momentum change which give raise to effects either in or against swimming direction (Matsuuchi et al. 2006); the saying 'push off from water' cannot be supported, even not for didactical purpose because 'giving way' is elementary for a fluid. Interest of non-steady flow phenomena can be extended to all activities in aquatic space and is not limited to sport swimming. Also when dealing with health related activities it is necessary to understand which momentum changes are involved when e.g. swinging the leg to and fro below waterline which is also accompanied by change of motion of water mass. In this text the aspects of non-steady flow physics will exemplified by a general situation of locomotion in water: the gliding after start and pushoff from a wall. lt seems as if everything is clear what happens: the speed of a swimmer will slow down according to the effect of drag. However, studies reveal that the data of gliding distance based on calculation using steady flow mechanics laws do not match with the data gained experimentally; swimmers glide further than calculated (Kiauck 1976). Consequently the drag of the gliding swimmer was modified by acceleration, called reaction-acceleration-force (AR). The surrounding water is also set in motion by the body movement relatively to the water which requires imparting momentum to displace the water in the body's path (Ungerechts 2003). The momentum change ofthe water masses can be observed as sloshing water if a swimmer has touched the wall at the end of a race and a little bit later waters sloshes on the wall. The water masses which were moved once by the body by frictional effects develop an independent way of motion ifthe bodies are slowing down e.g. due to gliding phase. Due to inertia ofthese moved water masses act as flywheel masses and continues to accelerate the body. lt is to be expected that a gliding person glides by effect of the ostensible additional masses differently compared to the easy acceptance that a steady and constant speed works. The purpose of this paper is to show a means to estimate AR by quantifying 'added mass'.